Mount Vernon: of workers and race. - Kelly, Elizabeth (My University, 2010)
The domestic artifacts of the Mount Vernon distillery site offer data on the lives of white workers. In comparing the domestic glass and ceramic artifacts of the distillery with comparable glass and ceramic data found at the slave site House for Families, the similarities and differences between the two groups can be seen. The artifact comparison may make it possible to determine if slave workers lived at the distillery along with the white workers. The artifact comparison showed that slaves and white workers were similar in being limited by their means. The existence of slave workers living at the distillery could not be determined at this time, however, potential areas for future analysis were presented.
Keywords: Excavations (Archaeology) -- Virginia -- Mount Vernon (Estate); Antiquities -- Virginia -- Mount Vernon (Estate)